“C’est la vie, c’est la narration”: The Reader in Christine Brooke-Rose’s Textermination and David Lodge’s Small World - Selejan Corina (American, British and Canadian Studies Journal, 2016)
This article considers two metafictional academic novels from the reader’s point of view. It argues that this critical vantage point is suggested (if not imposed) by the fictional texts themselves. The theoretical texts informing this reading pertain either to reader response or to theories of metafiction, in an attempt to uncover conceptual commonalities between the two. Apart from a thematic focus on academic conferences as pilgrimages and the advocacy of reading as an ethically valuable activity, the two novels also share a propensity for intertextuality, a blurring of the boundaries between fictional and critical discourse, as well as a questioning of the borderline between fiction and reality. The reading of fiction is paralleled to the reading of (one’s own) life and self-reflexivity emerges as crucial to both types of literacy.